Transcriptome and single-cell analysis reveal the contribution of immunosuppressive microenvironment for promoting glioblastoma progression - Ni, Lulu; Sun, Ping; Zhang, Sujuan; Qian, Bin; Chen, Xu; Xiong, Mengrui; Li, Bing (Frontiers in Immunology, 2023)
Graphical Abstract Overview of the study design. (A) We firstly identified five GBM progression related pathways. By performing functional enrichment analysis on gene sets obtained from three perspectives, such as genes co-survival in TCGA-GBM and CGGA cohort, DEGs of high and low risk groups, and DEGs of IDH1 mutation compared with wild type, we identified five pathways significantly associated with poor prognosis in GBM patients. (B) Secondly, GBM TME-associated functional gene signatures were constructed. Based on the activity profile of these signatures, GBM patients were classified into four distinct subtypes and immunosuppressive subtypes were found. (C) the expression of hub genes from immunosuppressive subtypes were validated in three single-cell RNA-seq datasets, and cell types significantly associated with TME subtypes were identified. The interactions between certain cell types were also elaborated.